Project on Human Development in Chicago Neighborhoods (PHDCN): Personal Identity, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Personal Identity instrument. It was administered to subjects in Cohorts 6, 9, 12, 15, and 18 and obtained information related to racial and ethnic identity, which was originally collected in PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): DEMOGRAPHIC FILE, WAVE 1, 1994-1997 (ICPSR 13581), and PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): DEMOGRAPHIC FILE, WAVE 2, 1997-2000 (ICPSR 13609). It also contained future orientation and discrimination questions, as well as questions relating to group importance that were drawn from the Puerto Rican Adolescent Survey.